A method for controlling grain boundaries and grain structure of matrix magnetic steel
Through high-temperature treatment and low-temperature rolling technology of carbon and silicon sources, the grain boundary and grain structure of neodymium-ferrobor magnets are optimized, and the problems of poor mechanical properties and insufficient thermal stability of neodymium-ferrobor magnets are solved, thus achieving high Yield and ultimate tensile strength and reduce production costs.
Patent Information
- Application Number
- CN202411241975.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The mechanical properties of neodymium iron boron matrix magnets have poor mechanical properties, insufficient thermal stability, high production costs, and the existing grain boundary and grain control technologies are difficult and costly.
Using high-temperature treatment of carbon and silicon sources, adding multi-diffusion powder, and after low-temperature rolling and firing, the grain boundaries and grain structure are controlled, the use of heavy rare earths is reduced, the grain orientation and size of magnetic steel is optimized, and the introduction of non-standard steel is introduced. Homogenized structure to improve interface and grain structure.
It improves the mechanical properties and thermal stability of magnets, reduces the negative impact of heavy rare earths on magnetic properties, reduces production costs, achieves high yield strength and ultimate tensile strength of magnets, and significantly increases Curie temperature.
Smart Images

Figure CN118762922B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials, and in particular relates to a method for controlling the grain boundary and grain structure of a base magnetic steel. Background Art
[0002] Magnet is a rare earth permanent magnet material with excellent magnetic properties. It is widely used in sensors, electronics, electromechanics, military and other fields, and plays an important role. The matrix magnet usually refers to NdFeB magnet. NdFeB magnet is one of the most magnetic permanent magnet materials known so far. It has a very high magnetic energy product, but its heat resistance is poor. Under normal circumstances, the Curie temperature is only 320-380 °C, and it will lose its magnetism quickly when working in a high-temperature environment. This has become a significant performance defect of NdFeB matrix magnets, but due to its excellent magnetic properties and the stability brought by its extremely high coercive force, how to improve the thermal stability of the matrix magnet has become an important research and development direction.
[0003] Current research shows that the most effective way to improve the thermal stability of the matrix magnetic steel is to adjust its performance by controlling the grain boundaries and grains, which can retain its magnetic properties to the greatest extent while effectively improving its thermal stability and even increasing its Curie temperature to a certain extent. Common methods include non-rare earth grain boundary diffusion technology and heavy rare earth grain boundary diffusion technology, which can change the wettability between the grain boundary phase and the grains and the number of defects, thereby improving the thermal stability of the matrix magnetic steel.
[0004] Grain boundaries and grain structure are key factors in determining the performance of matrix magnetic steel. Grain boundaries are the dividing lines between adjacent grains inside a crystal, and grains are the smallest units that make up metal materials. The properties of grain boundaries and the size, shape, and distribution of grains will have an important impact on the mechanical properties, magnetic properties, and the like of the material. In this field, heavy rare earths are usually distributed on the surface of magnetic steel. Since the diffusion temperature is higher than the melting point of the rare earth-rich grain boundary phase of the magnetic steel, the heavy rare earths diffuse along the grain boundaries into the interior of the magnetic steel and are distributed on the grain boundaries and grain surfaces. However, heavy rare earths can have an adverse effect on the environment and significantly increase the cost of preparing magnetic steel.
[0005] At the same time, the production of existing magnetic steel usually requires high temperature treatment. High temperature treatment cannot eliminate the transverse grain boundaries and cannot control the grain orientation of the solidified structure, resulting in poor longitudinal mechanical properties of the magnetic steel. Long-term use of high-temperature treated magnetic steel will cause cracking and falling of the magnetic steel, resulting in a significant decrease in its performance. In addition, the local enrichment of a certain element in the magnetic steel will lead to consistency deviation in the magnetic steel, thus affecting the performance of the magnetic steel.
[0006] In order to solve these problems, it is urgent to develop a method that takes into account the magnetic properties, mechanical properties and preparation cost of magnetic steel. Summary of the invention
[0007] In order to solve the problems of poor mechanical properties of existing NdFeB matrix magnets, inability to balance coercivity and magnetic properties, general lack of good thermal stability, and high cost and difficulty in existing grain boundary and grain control, the present invention proposes a method for controlling the grain boundaries and grain structure of matrix magnets.
[0008] 1. Improve the mechanical properties and thermal stability of magnetic steel;
[0009] 2. Control the grain orientation and size of the solidified structure, change the distribution and density of the grain boundary phase, and improve the intrinsic coercive force and maximum magnetic energy product of the magnetic steel;
[0010] 3. While effectively improving the coercive properties of magnetic steel, it greatly reduces the negative impact of heavy rare earth on remanence and magnetic energy product, and reduces the production cost of magnetic steel.
[0011] To achieve the above purpose, the present invention specifically adopts the following scheme.
[0012] A method for controlling the grain boundary and grain structure of a base magnetic steel,
[0013] The method comprises:
[0014] 1) Mix the carbon source and silicon source and treat at high temperature, add multi-element diffusion powder and mix evenly, and obtain multi-element diffusion material after heat treatment;
[0015] 2) In the mold, multi-element diffusion material, raw material powder and grain control particles are laid and oriented respectively, and a rough magnetic steel blank is obtained through low temperature rolling treatment;
[0016] 3) The rough magnetic steel billet is fired, rolled and the deformation is controlled, and then a secondary firing and tempering treatment is performed to complete the grain boundary and grain structure regulation to obtain the magnetic steel.
[0017] As a preference,
[0018] Step 1) the carbon source is carbon powder;
[0019] Step 1) The silicon source is silicon powder, and the amount thereof is 2.4-2.6 g / g carbon source;
[0020] The high temperature treatment in step 1) is a constant temperature treatment at 1410-1450°C for 1.0-1.5 h.
[0021] As a preference,
[0022] Step 1) the multi-element diffusion powder is a mixed powder of aluminum, copper and neodymium;
[0023] The dosage of the multi-element diffusion powder is 0.4-0.6 g / g carbon source, wherein aluminum, copper and neodymium are prepared in a mass ratio of (8-9): (1-2.5):1.
[0024] As a preference,
[0025] Step 1) The heat treatment is carried out at 740-880°C for 1-1.5 hours.
[0026] As a preference,
[0027] In step 2), when laying the multi-element diffusion material, raw material powder and grain control particles, one of the following two methods is used:
[0028] Method 2-a): Mix the multi-element diffusion material, raw material powder and grain control particles evenly and lay them in a mold;
[0029] Method 2-b): 45-55 wt% of raw material powder and 45-55 wt% of grain control particles are mixed and evenly distributed on the bottom layer of the mold, the multi-component diffusion material is laid thereon, and the remaining raw material powder and grain control particles are evenly distributed on the multi-component diffusion material.
[0030] As a preference,
[0031] The raw material powder is a mixed powder, and the mixed powder components are:
[0032] Nd 11.8~12.2 at%, Co 1.3~1.5 at%, Al-Cr0.2~0.4 at%, B 1.0~1.8 at%, the balance is Fe; wherein the Al-Cr alloy is an important alloy system, and its component ratio has a significant effect on the properties of the alloy. In the Al-Cr alloy, the atomic ratio of Al and Cr is usually 3:7 by default.
[0033] The amount of the raw material powder is 5.4-6.3 g / g carbon source;
[0034] The grain control particles are a mixed powder of titanium powder and terbium powder;
[0035] The dosage of the grain control particles is 0.4-0.6 g / g carbon source, wherein the mass ratio of titanium powder to terbium powder is 1:(0.1-0.2).
[0036] As a preference,
[0037] Step 2) the orientation is placed in a 1.3-1.6 T magnetic field for 25-30 min;
[0038] Step 2) The low temperature rolling treatment is performed at 80-90°C, at a pressure of 10-20 MPa, and with a deformation of 10-15%.
[0039] As a preference,
[0040] Step 3) the firing is performed at 300-320°C for 1.5-2 hours;
[0041] Step 3) The rolling deformation is 20-25%.
[0042] As a preference,
[0043] Step 3) the secondary firing is performed at 360-380°C for 1.5-2 h;
[0044] Step 3) The tempering treatment is carried out at 320-340°C for 4-5 hours.
[0045] In this field, excellent magnetic properties are usually obtained through the neodymium phase. In order to prepare magnetic steel with higher magnetocrystalline anisotropy field and higher coercivity, heavy rare earth elements are usually added. The more common heavy rare earth elements are terbium (Tb) and dysprosium (Dy). Adding terbium and dysprosium through traditional smelting methods can improve the magnetocrystalline anisotropy field of the neodymium phase, but due to the antiferromagnetic coupling between heavy rare earth atoms and iron atoms, the remanence and magnetic energy product of the magnetic steel will be reduced.
[0046] During the research process, it was found through experiments that adding an appropriate amount of cobalt (Co) during the preparation process can increase the maximum operating temperature of the magnetic steel. This is because Co atoms preferentially occupy the 8j1 crystal position of the NdFeB compound, reducing the negative exchange of the 8j1 atom pair (negative exchange of Fe-Fe atom pairs), reducing the negative temperature coefficient of the magnetic steel, enhancing its high temperature stability, and having little effect on the remanence. At the same time, some terbium-rich RE 3 Fe 4 For RE 3 Co 4 Transform and form RE 3 (Fe, Co) 4 Grain boundary phase, and form a certain amount of iron-cobalt soft magnetic phase, which changes the magnetic domain structure of the matrix magnetic steel and the diffusivity and solubility of the doping elements in the grain boundary.
[0047] In order to optimize the magnetic properties, the present invention also uses some Al-Cr and grain control particles. In previous studies and characterizations, it was found that Al, Cu, and Al-Cr in magnetic steel are mainly enriched in terbium-rich RE 3 (Fe, Co) 4 Grain boundary phase, non-magnetic atoms dissolved in the grain boundary phase enhance the demagnetization coupling effect of the grain boundary, ensuring that the magnetic steel has high coercivity, and the addition of Co element affects the grain boundary diffusion effect and solubility of this type of non-magnetic atoms. At the same time, with the increase of cobalt content, the coercivity of the magnetic steel changes little because the grain boundary optimization phases such as Al, Cu, Al-Cr improve the magnetic isolation properties of the grain boundary phase; Cobalt reduces the solid solubility of low melting point elements in the grain boundary phase, and each element tends to be evenly distributed.
[0048] However, when excessive cobalt powder is added, the main phase RE in the magnetic steel 2 (Fe, Co) 14 The B phase forms a large number of easily demagnetized areas in the magnetic steel, resulting in a decrease in the coercive force of the magnetic steel; it causes microstructural deterioration problems such as the missing of thin-layer grain boundary phases, coarse triple grain boundaries, and the formation of Co-rich soft magnetic phases. The trend of coercive force decreases far exceeds the trend of remanence temperature coefficient decreases, resulting in a rapid decrease in the coercive force of the matrix magnetic steel.
[0049] In addition, according to the research of those skilled in the art, the properties of grain boundaries and grain size determine the mechanical properties of the material, and the key is to control the interface structure and grain structure. In the technical solution of the present invention, a non-homogeneous structure is introduced to regulate the interface structure and grain structure of the magnetic steel, improve the above problems, and improve the mechanical properties of the magnetic steel. That is, at high temperatures, whisker-like β-SiC is successfully synthesized to ensure that metal particles can diffuse from the pores formed by the whisker-like β-SiC into the interior of the magnetic steel, that is, a diffusion channel for metal particles is constructed, thereby improving the interface performance of the magnetic steel. However, at too low a temperature, the purity of β-SiC is low, and even no carbonization reaction occurs. Although β-SiC whiskers grow along the
[111] direction, some irregular stacking defects and twin defects will appear, resulting in poor grain boundary quality, but the problems caused by such defects can be improved after thermal diffusion of SiC and metal powder. This is because the introduction of β-SiC can provide favorable growth points for grains, and the defective structure on the surface of a small amount of β-SiC provides favorable conditions for the combination of C-Al. The enhanced bonding effect is also conducive to transferring the stress on β-SiC, repairing the grain boundary quality, and significantly improving the strength of the material. At the same time, due to the Si-Si bond, β-SiC is difficult to decompose Si atoms, further improving the stability. However, when Si powder particles are affected by excessive other metals and the bond length between Si and Si atoms is elongated, although the transformation of Si to β-SiC is promoted, the bonding strength of Si-Si bonds will be significantly reduced, and excessive C-Al will cause severe brittle fracture. It can be seen from this that it is obviously necessary to control the composition and dosage of multi-diffusion particles relative to carbon sources and silicon sources.
[0050] In addition to repairing the grain boundary defects caused by β-SiC, the multi-diffusion particles (Al-Cu-Nd) used also have the characteristics of low melting point, which plays a certain role as a lubricant, which is conducive to the wetting, flow and uniform distribution of the neodymium-rich phase along the main phase particles during heat treatment. In addition, Al-Cu-Nd is attached to the β-SiC whiskers, and the two diffuse and react with each other to form a compound with high adhesion strength, so that the material maintains toughness. Since Al-Cu-Nd is distributed both in the β-SiC whiskers and around the interface, when the material is stretched, the fine grains relieve stress concentration, eliminate the initial crack source under tensile conditions, and enhance the toughness and tensile strength of the material. However, the use of excessive Al-Cu-Nd will lengthen the bond length between Si atoms as mentioned above, resulting in a significant decrease in the bonding strength between Si atoms, thereby causing the Al-Cu-Nd particles to fall off.
[0051] In the process of metal element diffusion, terbium can significantly improve the high temperature stability of the material, preferentially enter the crystal phase, and further introduce titanium powder, thereby improving the mechanical properties of the material. The magnetic moment of neodymium atoms is consistent with the magnetic moment of iron atoms, while the magnetic moment of terbium atoms is opposite to the magnetic moment of iron atoms, which will reduce the total saturation magnetization intensity. Therefore, the present invention controls its dosage and uses a very small amount of terbium, which can also reduce the manufacturing cost of the magnet.
[0052] When terbium enters the main phase, the volume fraction of the grain boundary phase and the magnetocrystalline anisotropy field are increased. According to the difference in the metal diffusion depth before and after the test, the diffusion direction of terbium can be seen, and more grain boundary phases are found to flow into the diffusion channel. At the same time, part of the terbium remains outside the main phase grains to form a thin layer of grain boundary phase. As mentioned above, the substitution of Co for Fe increases the width of the thin layer of grain boundary phase, improves the demagnetization coupling ability of the grain boundary, and greatly improves the coercive force of the magnetic steel.
[0053] In addition, the coarse grain area in the magnetic steel has a greater influence on the magnetic properties. In synergistic with the multi-diffusion powder, the present invention also regulates the grain size through processing methods, promotes the distribution of metal elements along the grain boundaries, and forms a network structure between the fine grains, which effectively hinders the movement of dislocations within the grains and further strengthens the grain boundaries. A large number of grain boundaries are generated in the networked material, which hinders the movement of dislocations, thereby increasing the yield strength of the material. In magnetic steel with uniform heterogeneous structure, the volume fraction of the soft zone increases. In this structure, the grain boundaries are greatly affected, and the soft zone is restricted by the hard zone. When subjected to tensile force, the magnetic steel can adapt to the local plastic strain gradient between the hard zone and the soft zone, promoting its high strain hardening.
[0054] The low-temperature hot pressing deformation (volume deformation, i.e., the volume reduction of the product obtained after pressing and molding compared to the loose volume of the raw material powder before hot pressing) and rolling deformation (volume deformation, i.e., the volume reduction of the product obtained after rolling compared to the volume of the sample before rolling) will affect the uniformity of the microstructure of the material and adjust the morphology of the particles in the matrix. The appropriate deformation can promote the elimination of segregation, reduce the banded structure formed by center segregation and component segregation in the material, and destroy the columnar structure, refine the grains, and preferentially grow the grains along the pressure direction, thereby enhancing the thermal shock resistance of the material. The present invention adjusts the heterogeneous structure through the deformation of hot pressing and rolling, and especially constructs a heterogeneous layered structure through subsequent rolling. The layered structure is composed of nanoparticles distributed in layers and grains of bimodal size. There are both slender coarse crystals and fine equiaxed crystals in the magnetic steel. During rolling, the particle distribution has a great influence on the grains of the magnetic steel. The average grain length of the slender coarse crystals is less than 8 μm, the width is less than 2 μm, and they are elongated along the extrusion direction. The fine equiaxed grains are mainly distributed around the grain boundaries, and the average grain size is also reduced.
[0055] The two laying methods provided by the present invention have a certain influence on the magnetic steel. The surface of the magnetic steel prepared by the laying method 2-a is weakly affected by the hard multi-element diffusion material, and the grains are easy to migrate and overgrow into non-oriented periodic coarse grain areas, thereby limiting the magnetic properties. The magnetic steel prepared by the laying method 2-b is more uniformly deformed, the grains are oriented parallel to the rolling direction, and finer equiaxed grains are presented near the grain boundary interface. The orientation degree of the magnetic steel prepared by the two laying methods differs by about 4.5%.
[0056] In order to ensure that the grains grow preferentially along the stress direction, the present invention rolls the material twice. The second rolling deformation can accumulate higher energy, promote the diffusion of alloy elements, and reduce banded structure. During the plastic deformation process, shear force is applied to the matrix of the composite material, and the coarse crystals flow by shear. At the same time, the network formed by the fine crystals is further expanded to form a micron-level network structure. With further deformation, the network structure is obviously dispersed and the particles are evenly distributed. Excessive rolling deformation cannot cause the material to recrystallize, and only flattening occurs. Therefore, there is no need to continue to increase the deformation.
[0057] Based on the above process, the present invention actually needs to strictly control the subsequent sintering temperature to avoid the loss of the grain boundary and grain structure advantages formed during the rolling process, because the high-temperature heat treatment process will cause the grains to grow again due to atomic diffusion, grain boundary migration, etc., and the present invention actually wants to construct the characteristics of polycrystalline and fine-grained grain structure, and form more favorable grain boundaries to improve the thermal stability of the base magnetic steel.
[0058] The beneficial effects of the present invention are as follows:
[0059] (1) The magnetic steel prepared by the present invention has a uniformly distributed fine-grained structure and a high grain boundary density;
[0060] (2) The yield strength of the magnetic steel exceeds 330 MPa, and the ultimate tensile strength exceeds 380 MPa, which has good mechanical properties;
[0061] (3) After treatment, the base magnetic steel still maintains good magnetic properties;
[0062] (4) The preparation method of the present invention reduces the negative impact of heavy rare earth on the magnetic properties of magnetic steel and reduces the production cost of magnetic steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is the metallographic spectrum of magnetic steel b prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0064] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0065] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0066] Example 1
[0067] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0068] 1) Take 10 g carbon powder and 24 g silicon powder and mix them evenly, keep the temperature at 1450 °C for 1 h, add 3.2 g aluminum powder, 0.4 g copper powder and 0.4 g neodymium powder and mix them evenly, keep the temperature at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0069] 2) Prepare two equal amounts of multi-element diffusion material samples by the method in step 1) above for later use, and then obtain magnetic steel blanks by the following laying methods respectively;
[0070] 2-a): A portion of the multi-element diffusion material prepared in step 1) is mixed evenly with 54 g of raw material powder, 4 g of titanium powder, and 0.6 g of terbium powder and placed in a mold, and oriented at a magnetic field strength of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 10%, to obtain a magnetic steel blank a;
[0071] The raw material powder comprises: Nd 11.8 at%, Co 1.3 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0072] 2-b) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay a portion of the multi-element diffusion material prepared in step 1) on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80°C and 10 MPa pressure, and the deformation is controlled to be 10%, to obtain a magnetic steel blank b;
[0073] The raw material powder comprises: Nd 11.8 at%, Co 1.3 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0074] 3) Take magnetic steel blanks a and b respectively, sinter them at 300 °C for 2 h, roll them and control the deformation to 20%, sinter them at 760 °C for 2 h, and temper them at 320 °C for 5 h to obtain magnetic steel a (corresponding to the product of magnetic steel blank a, the same below) and magnetic steel b (corresponding to the product of magnetic steel blank b, the same below).
[0075] The two magnetic steels obtained in this example were subjected to mechanical property tests and magnetic property characterization. In addition, the grains of magnetic steel b were also characterized and tested, such as Figure 1 As shown in the characterization diagram, the grain size of the magnetic steel b in this example can reach about 2 μm, with clear grain boundaries, almost no white impurity phase formed, and highly uniform grain composition. The same characterization was performed on the magnetic steel a, and the results showed that its grains were relatively large, about 2.2 to 2.3 μm, and a small amount of white impurity phase coarse crystals appeared, which would have a certain impact on the performance of the base magnetic steel.
[0076] 1. Mechanical properties:
[0077] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0078] 2. Magnetic properties characterization:
[0079] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BH max ) for characterization.
[0080] The results are as follows.
[0081]
[0082] From the characterization results in the above table, it can be clearly seen that the magnetic steel obtained in this example has good mechanical properties and magnetic properties, and both have very excellent thermal stability. In terms of magnetic properties, the magnetic steel obtained by the present invention is very close to the existing NdFeB properties, indicating that the process of the present invention introduces non-magnetic atoms to improve and optimize the grain boundaries and grain structure of the magnetic steel, and does not have a significant negative impact on the magnetic properties, and basically effectively retains the magnetic properties. In terms of mechanical properties, the present invention has also achieved the level of high-quality NdFeB magnets by optimizing the grain boundaries and grain structure using an effective method. In terms of thermal stability, it is particularly outstanding. Among them, the Curie temperature of magnetic steel a reaches at least 400 ° C, and magnetic steel b can even reach at least 420 ° C, which is far better than the Curie temperature of the existing NdFeB magnet of about 360 to 380 ° C, showing excellent high temperature resistance. On the other hand, the magnetic properties at different temperatures also show that both magnetic steel a and magnetic steel b in this example can maintain extremely high remanence strength, coercive force and maximum magnetic energy product at 220 °C. Compared with room temperature (25 °C), the remanence strength, in particular, has not decreased significantly, showing extremely excellent thermal stability, and the thermal stability of magnetic steel b is more significantly better than that of magnetic steel a. This is because the surface of the magnetic steel prepared by the laying method of method 2-a is weakly affected by the hard multi-element diffusion material, and the grains are easy to migrate and overgrow into non-oriented periodic coarse grain areas, thereby limiting the magnetic properties, while the magnetic steel prepared by the laying method of method 2-b is more uniform after deformation, the grains are oriented parallel to the rolling direction, and a finer grain structure is presented near the grain boundary interface, with less impurities and more stable performance.
[0083] Therefore, for the technical solution of the present invention, the preparation method of magnetic steel b is the best result. Unless otherwise specified, the subsequent embodiments and comparative examples all adopt the laying form of method 2-b to prepare the base magnetic steel and realize the regulation of the grain boundary and grain structure of the base magnetic steel during the preparation process.
[0084] Example 2
[0085] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0086] 1) Take 10 g carbon powder and 24 g silicon powder and mix them evenly, keep the temperature at 1450 °C for 1 h, add 4.0 g aluminum powder, 0.5 g copper powder and 0.5 g neodymium powder and mix them evenly, keep the temperature at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0087] 2) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay the multi-element diffusion material on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 10% to obtain a rough magnetic steel blank;
[0088] The raw material powder comprises: Nd 11.8 at%, Co 1.3 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0089] 3) Take the magnetic steel blank, fire it at 300 °C for 2 h, roll it and control the deformation to 20%, fire it at 760 °C for 2 h, and temper it at 320 °C for 5 h to obtain the magnetic steel.
[0090] The two types of magnetic steel obtained in this example were subjected to mechanical property testing and magnetic property characterization.
[0091] 1. Mechanical properties:
[0092] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0093] 2. Magnetic properties characterization:
[0094] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BH max ) for characterization.
[0095] The results are as follows.
[0096]
[0097] It can be clearly seen from the above characterization results that the mechanical properties of this example are slightly improved compared with Example 1, while the magnetic properties are very close, with almost no change, some slightly improved, some slightly decreased, and basically flat. This shows that the Al-Cu-Nd alloy nanoparticles attached to the whiskers can promote the wetting, flow, and uniform distribution of the neodymium-rich phase along the main phase particles, and its bonding strength is high, which is conducive to further optimization and improvement of the mechanical properties of the magnet.
[0098] Example 3
[0099] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0100] 1) Take 10 g carbon powder and 24 g silicon powder and mix them evenly, keep the temperature at 1450 °C for 1 h, add 4.8 g aluminum powder, 0.6 g copper powder and 0.6 g neodymium powder and mix them evenly, keep the temperature at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0101] 2) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay the multi-element diffusion material on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 10% to obtain a rough magnetic steel blank;
[0102] The raw material powder comprises: Nd 11.8 at%, Co 1.3 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0103] 3) Take the magnetic steel blank, fire it at 300 °C for 2 h, roll it and control the deformation to 20%, fire it at 760 °C for 2 h, and temper it at 320 °C for 5 h to obtain the magnetic steel.
[0104] The two types of magnetic steel obtained in this example were subjected to mechanical property testing and magnetic property characterization.
[0105] 1. Mechanical properties:
[0106] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0107] 2. Magnetic properties characterization:
[0108] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BH max ) for characterization.
[0109] The results are as follows.
[0110]
[0111] It can be clearly seen from the above characterization results that more Al-Cu-Nd alloy is used for multi-element diffusion in this example, which leads to a negative impact on the thin layer grain boundary phase in this material, because the proportion of Co is not increased accordingly during the preparation process of this example, and Co itself can affect the solid solubility of Al-Cu-Nd alloy at the grain boundary to a certain extent, thus causing a certain uneven distribution of Al-Cu-Nd, poor demagnetization coupling ability of the grain boundary, and a slight decrease in its coercive force.
[0112] Example 4
[0113] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0114] 1) Take 10 g carbon powder and 24 g silicon powder and mix them evenly, keep the temperature at 1450 °C for 1 h, add 4.0 g aluminum powder, 0.5 g copper powder and 0.5 g neodymium powder and mix them evenly, keep the temperature at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0115] 2) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay the multi-element diffusion material on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 10% to obtain a rough magnetic steel blank;
[0116] The raw material powder comprises: Nd 11.8 at%, Co 1.5 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0117] 3) Take the magnetic steel blank, fire it at 300 °C for 2 h, roll it and control the deformation to 20%, fire it at 760 °C for 2 h, and temper it at 320 °C for 5 h to obtain the magnetic steel.
[0118] The two types of magnetic steel obtained in this example were subjected to mechanical property testing and magnetic property characterization.
[0119] 1. Mechanical properties:
[0120] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0121] 2. Magnetic properties characterization:
[0122] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BHmax ) for characterization.
[0123] The results are as follows.
[0124]
[0125] It can be clearly seen from the above characterization results that this example uses raw material powder with a higher cobalt content as the matrix on the basis of Example 2. Generally speaking, cobalt can optimize the mechanical properties and hardness of the magnet, but for the technical solution of the present invention, cobalt is not a single factor affecting mechanical properties. It also affects the Al-Cu-Nd alloy and has a correlation. Therefore, although the cobalt content is relatively increased in this example, the mechanical properties are not improved, and even the yield strength and surface hardness are reduced. This is because Co affects the diffusion depth and solid solubility of the alloying elements. However, in terms of thermal stability, it can be seen that this example is slightly improved.
[0126] Comparative Example 1
[0127] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0128] 1) Take 10 g carbon powder and 24 g silicon powder and mix them evenly, keep the temperature at 1450 °C for 1 h, add 4.0 g aluminum powder, 0.5 g copper powder and 0.5 g neodymium powder and mix them evenly, keep the temperature at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0129] 2) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay the multi-element diffusion material on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 10% to obtain a rough magnetic steel blank;
[0130] The raw material powder comprises: Nd 11.8 at%, Co 1.8 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0131] 3) Take the magnetic steel blank, fire it at 300 °C for 2 h, roll it and control the deformation to 20%, fire it at 760 °C for 2 h, and temper it at 320 °C for 5 h to obtain the magnetic steel.
[0132] The two types of magnetic steel obtained in this example were subjected to mechanical property testing and magnetic property characterization.
[0133] 1. Mechanical properties:
[0134] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0135] 2. Magnetic properties characterization:
[0136] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BH max ) for characterization.
[0137] The results are as follows.
[0138]
[0139] It can be clearly seen from the above characterization results that excessive cobalt was added in this case, resulting in the main phase RE in the matrix magnetic steel 2 (Fe, Co) 14 The B phase forms a large number of easily demagnetized areas in the magnetic steel, resulting in the deterioration of the microstructure such as the reduction of the coercivity of the magnetic steel, the loss of thin-layer grain boundary phase, the coarsening of triple grain boundaries, the formation of Co-rich soft magnetic phase, etc. The trend of the coercivity decrease far exceeds the trend of the remanence temperature coefficient decrease, resulting in a significant decrease in the coercivity of the prepared magnetic steel. The excessive cobalt even has a great influence on the diffusion and solid solution of non-magnetic atoms, and has a certain impact on the Curie temperature of the material.
[0140] Comparative Example 2
[0141] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0142] 1) 4.0 g aluminum powder, 0.5 g copper powder and 0.5 g neodymium powder were mixed evenly and kept at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0143] 2) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay the multi-element diffusion material on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 10% to obtain a rough magnetic steel blank;
[0144] The raw material powder comprises: Nd 11.8 at%, Co 1.3 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0145] 3) Take the magnetic steel blank, fire it at 300 °C for 2 h, roll it and control the deformation to 20%, fire it at 760 °C for 2 h, and temper it at 320 °C for 5 h to obtain the magnetic steel.
[0146] The two types of magnetic steel obtained in this example were subjected to mechanical property testing and magnetic property characterization.
[0147] 1. Mechanical properties:
[0148] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0149] 2. Magnetic properties characterization:
[0150] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BH max ) for characterization.
[0151] The results are as follows.
[0152]
[0153] It can be clearly seen from the above characterization results that in this example, the absence of whisker-like SiC (β-SiC) and Al-Cu-Nd to form a multi-diffusion powder resulted in a significant decrease in the mechanical and magnetic properties of the magnetic steel. This is because β-SiC also has a significant effect on the diffusion and distribution of Al-Cu-Nd. β-SiC can construct a diffusion channel for metal elements and can cooperate with metal elements to repair the grain boundaries of the magnetic steel, making the grain boundaries clearer and more complete. Without the addition of β-SiC, the diffusion difficulty of metal elements increases, the depth decreases, and a certain degree of disorder or even segregation occurs, which has a significant impact on the performance of the magnetic steel.
[0154] Comparative Example 3
[0155] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0156] 1) Take 10 g carbon powder and 24 g silicon powder and mix them evenly, keep the temperature at 1450 °C for 1 h, add 4.0 g aluminum powder, 0.5 g copper powder and 0.5 g neodymium powder and mix them evenly, keep the temperature at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0157] 2) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay the multi-element diffusion material on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 5% to obtain a rough magnetic steel blank;
[0158] The raw material powder comprises: Nd 11.8 at%, Co 1.3 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0159] 3) Take the magnetic steel blank, fire it at 300 °C for 2 h, roll it and control the deformation to 20%, fire it at 760 °C for 2 h, and temper it at 320 °C for 5 h to obtain the magnetic steel.
[0160] The two types of magnetic steel obtained in this example were subjected to mechanical property testing and magnetic property characterization.
[0161] 1. Mechanical properties:
[0162] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0163] 2. Magnetic properties characterization:
[0164] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BH max ) for characterization.
[0165] The results are as follows.
[0166]
[0167] In this example, the deformation of the first low-temperature rolling was only 5%. Characterization revealed that the degree of grain migration of the material was small, segregation of neodymium elements occurred, and banded structure was formed, that is, uneven composition. Although this did not have a very significant effect on the direct mechanical properties and magnetic properties of the magnet, it was found in an additional thermal shock test (20 ℃-220 ℃ thermal shock test, holding time 5min, 120 cycles) that its magnetic properties and mass loss rate were much higher than those of the sample prepared in Example 2, with the magnetic properties decreasing by about 336% of that of the sample in Example 2, and the mass loss rate even reaching about 513% of that of the sample in Example 2, indicating that the structural stability and density of the sample also decreased significantly due to the decrease in uniformity.
[0168] Comparative Example 4
[0169] A method for controlling grain boundaries and grain structures of a base magnetic steel, the method comprising:
[0170] 1) Take 10 g carbon powder and 24 g silicon powder and mix them evenly, keep the temperature at 1450 °C for 1 h, add 6.0 g aluminum powder, 1.5 g copper powder and 0.5 g neodymium powder and mix them evenly, keep the temperature at 740 °C for 1.5 h to obtain a multi-element diffusion material;
[0171] 2) Take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the bottom layer of the mold, lay the multi-element diffusion material on it, and then take 27 g of raw material powder, 2 g of titanium powder, and 0.3 g of terbium powder, mix them and evenly distribute them on the multi-element diffusion material, and orient them at a magnetic field intensity of 1.6 T for 25 min. During the orientation process, low-temperature hot pressing is performed at 80 ° C and 10 MPa pressure, and the deformation is controlled to be 10% to obtain a rough magnetic steel blank;
[0172] The raw material powder comprises: Nd 11.8 at%, Co 1.3 at%, Al-Cr 0.2 at%, B 1.2 at%, and the balance is Fe;
[0173] 3) Take the magnetic steel blank, fire it at 300 °C for 2 h, roll it and control the deformation to 20%, fire it at 760 °C for 2 h, and temper it at 320 °C for 5 h to obtain the magnetic steel.
[0174] The two types of magnetic steel obtained in this example were subjected to mechanical property testing and magnetic property characterization.
[0175] 1. Mechanical properties:
[0176] The bending strength, tensile strength, surface hardness and Curie temperature (testing with a gradient of 20 °C and recording the highest undemagnetized temperature) of the material were tested and characterized, and the average values were recorded.
[0177] 2. Magnetic properties characterization:
[0178] At different temperatures, the remanence (Br), intrinsic coercivity (Hcj), and maximum magnetic energy product (BH max ) for characterization.
[0179] The results are as follows.
[0180]
[0181] It can be clearly seen from the above characterization results that the thermal stability of the magnetic steel prepared in this example is significantly reduced. The reason is that too much Al-Cu elements change the insertion form of the original Al-Cu-Nd and Nd on β-SiC, which affects β-SiC. The Si-Si bond length is elongated and the bonding strength between Si atoms is significantly reduced, which causes the Al-Cu-Nd alloy particles to fall off and cannot be effectively assisted by diffusion through β-SiC, which ultimately leads to a decrease in the uniformity of its component distribution.
Claims
1. A method for controlling the grain boundary and grain structure of a base magnetic steel, characterized in that: The method comprises: 1) Mix the carbon source and silicon source and treat at high temperature, add multi-element diffusion powder and mix evenly, and obtain multi-element diffusion material after heat treatment; 2) In the mold, multi-element diffusion material, raw material powder and grain control particles are laid and oriented respectively, and a rough magnetic steel blank is obtained through low temperature rolling treatment; 3) The rough magnetic steel billet is fired, rolled and the deformation is controlled, and then the secondary firing and tempering are performed to complete the grain boundary and grain structure regulation to obtain the magnetic steel; Step 1) the carbon source is carbon powder; Step 1) The silicon source is silicon powder, and the amount thereof is 2.4-2.6 g / g carbon source; Step 1) The high temperature treatment is carried out at a constant temperature of 1410-1450°C for 1.0-1.5 h; Step 1) the multi-element diffusion powder is a mixed powder of aluminum, copper and neodymium; The amount of the multi-element diffusion powder is 0.4-0.6 g / g carbon source, wherein aluminum, copper and neodymium are prepared in a mass ratio of (8-9): (1-2.5): 1; The raw material powder is a mixed powder, and the mixed powder components are: Nd 11.8~12.2 at%, Co 1.3~1.5 at%, Al-Cr 0.2~0.4 at%, B 1.0~1.8 at%, the balance is Fe; The amount of the raw material powder is 5.4-6.3 g / g carbon source; The grain control particles are a mixed powder of titanium powder and terbium powder; The dosage of the grain control particles is 0.4-0.6 g / g carbon source, wherein the mass ratio of titanium powder to terbium powder is 1:(0.1-0.2).
2. The method for controlling the grain boundary and grain structure of a base magnetic steel according to claim 1, characterized in that: Step 1) The heat treatment is carried out at 740-880°C for 1-1.5 hours.
3. The method for controlling grain boundaries and grain structure of a base magnetic steel according to claim 1, characterized in that: In step 2), when laying the multi-element diffusion material, raw material powder and grain control particles, one of the following two methods is used: Method 2-a): Mix the multi-component diffusion material, raw material powder and grain control particles evenly and lay them in a mold; Method 2-b): 45-55 wt% of raw material powder and 45-55 wt% of grain control particles are mixed and evenly distributed on the bottom layer of the mold, the multi-component diffusion material is laid thereon, and the remaining raw material powder and grain control particles are evenly distributed on the multi-component diffusion material.
4. The method for controlling grain boundaries and grain structure of a base magnetic steel according to claim 1, characterized in that: Step 2) the orientation is placed in a 1.3-1.6 T magnetic field for 25-30 min; Step 2) The low temperature rolling treatment is performed at 80-90°C, at a pressure of 10-20 MPa, and with a deformation of 10-15%.
5. The method for controlling grain boundaries and grain structure of a base magnetic steel according to claim 1, characterized in that: Step 3) the firing is performed at 300-320°C for 1.5-2 hours; Step 3) The rolling deformation is 20-25%.
6. A method for controlling grain boundaries and grain structures of a base magnetic steel according to claim 1 or 5, characterized in that: Step 3) the secondary firing is performed at 760-780°C for 1.5-2 hours; Step 3) The tempering treatment is carried out at 320-340°C for 4-5 hours.
Citation Information
Patent Citations
Grain boundary phase-reconstructed high-corrosion resistance Sintered NdFeB magnet and preparation method thereof
CN101320609A